Workaholism in IT: An analysis of the influence factors - Octavian Dospinescu; Nicoleta Dospinescu (Administrative Sciences, 2020)
The purpose of this article is to make an exhaustive analysis of the influencing factors for the phenomenon of workaholism in IT. In contemporary economies, workaholism is an increasingly common phenomenon. Companies should evaluate the impact on workers of this trend, and note that knowledge of the factors influencing the decision to overwork can be a competitive advantage when implementing human resources policies. Our approach involved the use of multivariate analysis of variance combined with multiple linear regression analysis. The article analyzes the data from 178 respondents who are employed in the IT sector in Romania, taking into account seven potential factors of influence. The data and econometric analyses were processed in IBM SPSS Software. The results of the multivariate analysis of variance combined with multiple linear regression analysis show a significant relationship between workaholism and influencing factors such as the remunerative component of work, the intrinsic pleasure of working, the sense of responsibility towards family, and the desire to develop during a professional career. In this study, socio-demographic influences were found to have a weak influence on the decision to work excessively.
Keywords: 350; workaholism; influence factors of workaholism; IT industry; workaholism in IT